The Developing Chinese Rehabilitation Medicine - Lidian CHEN; Jian'an LI (康复学报)
The rapid developments of China's economy and society have brought tremendous demands for rehabilitation services. Chinese rehabilitation medicine(CRM)faces both opportunities and challenges. In the process of rapid development, with a good policy environment, CRM has made a series of achievements. Great progress has been made in the service system construction, rehabilitation technology and scientific research. Looking forward to the future, there is broad development space for CRM. It will continuously play an active role in preventing and mitigating disability, promoting recovery of physical and mental dysfunction, improving overall health and national economic growth.